Analysing students' content-learning in science in CLIL vs. non-CLIL programmes: empirical evidence from Spain - Fernández-Sanjurjo, Javier; Fernández-Costales, Alberto; Arias Blanco, José Miguel (International journal of bilingual education and bilingualism, 2019)
This paper investigates students' performance in content-subjects in the framework of CLIL programmes in Spain. So far, CLIL research has focused primarily on language attainment in the L2 and the L1, but students' achievements as regards content-subjects have been largely ignored. Competence in Science in the L1 is analysed by comparing pupils enrolled in mainstream schools with students in the so-called 'bilingual streams' offering CLIL-based approaches. The main objective is to assess if students learning Science through the L2 (English) outperform their counterparts studying in the L1 (Spanish) as regards content acquisition. The paper analyses a sample of 709 6th grade Primary Education students enrolled in public schools in the Principality of Asturias (Spain). A test to assess students' knowledge in Science and a context questionnaire (measuring participants' socio-economic status) were designed. The main finding is that students learning contents in their L1 perform slightly better than those studying Science through the L2. Furthermore, participants with lower socio-economic status obtain lower scores than those coming from more privileged backgrounds.